Influence of microstructures on mechanical behaviours of SiC nanowires: a molecular dynamics study - Wang, Jun; Lu, Chungsheng; Wang, Q.; Xiao, P.; Ke, F.; Bai, Y.; Shen, Y.; Liao, X.; Gao, H. (Institute of Physics Publishing Ltd., 2012)
The tensile behaviours of [111]-oriented SiC nanowires with various microstructures areinvestigated by using molecular dynamics simulations. The results revealed the influence ofmicrostructures on brittleness and plasticity of SiC nanowires. Plastic deformation is mainlyinduced by the anti-parallel sliding of 3C−grains along an intergranular amorphous film parallel tothe (111) plane and inclined at an angle of 19.47º with respect to the nanowire axis. Our studysuggests that the wide dispersion of mechanical properties of SiC nanowires observed in experiments might be attributed to their diverse microstructures.